Theoretical study for magnetic effect in dissociative adsorption of oxygen to a platinum monolayer on Ni(110) surface - Rahman, Md. Mamudur; Muhida, Rifki; Chowdhury, M. S. H.; Zainuddin, Hishamuddin; Zakaria, Azmi; Kasai, Hideaki (Elsevier B.V., 2012)
We investigate oxygen dissociative adsorption to a platinum monolayer on Ni(110) surface (Pt/Ni(110))by density functional theory. We have shown that the activation barrier on Pt/Ni(110) is lower than that on a clean Pt(001) surface. This may be due to the effect of magnetization of Pt surface. The reason of decrease of activation barrier can be attributed to the flow of electrons from oxygen to platinum surface because the d orbitals have spin polarization at the Fermi level where the down spin d orbitals are unoccupied.